Interactions between Procedural Learning and Cocaine Exposure Alter Spontaneous and Cortically Evoked Spike Activity in the Dorsal Striatum - Ondracek, Janie; Willuhn, Ingo; Steiner, Heinz; West, Anthony R. (Frontiers in Neuroscience, 2010)
We have previously shown that cocaine enhances gene regulation in the sensorimotor striatum associated with procedural learning in a running-wheel paradigm. Here we assessed whether cocaine produces enduring modifications of learning-related changes in striatal neuron activity, using single-unit recordings in anesthetized rats 1 day after the wheel training. Spontaneous and cortically-evoked spike activity was compared between groups treated with cocaine or vehicle immediately prior to the running-wheel training or placement in a locked wheel (control conditions). We found that wheel training in vehicle-treated rats increased the average firing rate of spontaneously active neurons without changing the relative proportion of active to quiescent cells. In contrast, in rats trained under the influence of cocaine, the proportion of spontaneously firing to quiescent cells was significantly greater than in vehicle-treated, trained rats. However, this effect was associated with a lower average firing rate in these spontaneously active cells, suggesting that training under the influence of cocaine recruited additional low-firing cells. Measures of cortically-evoked activity revealed a second interaction between cocaine treatment and wheel training, namely, a cocaine-induced decrease in spike onset latency in control rats (locked wheel). This facilitatory effect of cocaine was abolished when rats trained in the running wheel during cocaine action. These findings highlight important interactions between cocaine and procedural learning, which act to modify population firing activity and the responsiveness of striatal neurons to excitatory inputs. Moreover, these effects were found 24 hours after the training and last drug exposure indicating that cocaine exposure during the learning phase triggers long-lasting changes in synaptic plasticity in the dorsal striatum. Such changes may contribute to the transition from recreational to habitual or compulsive drug taking behavior.